Human Papillomavirus neutralizing and cross-reactive antibodies induced in HIV-positive subjects after vaccination with quadrivalent and bivalent HPV vaccines. Issue 13 (18th March 2016) - Faust, Helena; Toft, Lars; Sehr, Peter; Müller, Martin; Bonde, Jesper; Forslund, Ola; Østergaard, Lars; Tolstrup, Martin; Dillner, Joakim
Highlights: Immunogenicity has emerged as an important outcome measure for HPV vaccine research. HIV-infected individuals received either Gardasil™ or Cervarix™ and Ab response was measured. Two HPV serology methods produced similar results for HPV immunogenicity. HPV vaccines were highly immunogenic in adult HIV-infected population. The results support HPV vaccination of HIV-positive adults. Abstract: Ninety-one HIV-infected individuals (61 men and 30 women) were randomized to vaccination either with quadrivalent (Gardasil™) or bivalent (Cervarix™) HPV vaccine. Neutralizing and specific HPV-binding serum antibodies were measured at baseline and 12 months after the first vaccine dose. Presence of neutralizing and binding antibodies had good agreement (average Kappa for HPV types 6, 11, 16, 18, 31, 33 and 45 was 0.65). At baseline, 88% of subjects had antibodies against at least one genital HPV. Following vaccination with Cervarix™, all subjects became seropositive for HPV16 and 18. After Gardasil™ vaccination, 96% of subjects seroconverted for HPV16 and 73% for HPV18. Levels of HPV16-specific antibodies were <1 international unit (IU) in 87% of study subjects before vaccination but >10 IU in 85% of study subjects after vaccination. Antibodies against non-vaccine HPV types appeared after Gardasil™ vaccination for >50% of vaccinated females for HPV 31, 35 and 73 and for >50% of Cervarix™-vaccinated females for HPV 31, 33, 35, 45, 56 and 58. Cross-reactivity with non-genital HPV types was also detected. In conclusion, HIV-infected subjects responded to HPV vaccination with induction of neutralizing antibodies against both vaccine and non-vaccine types.